Third dose of COVID-19 mRNA vaccine closes the gap in immune response between naïve nursing home residents and healthy adults. Issue 17 (24th April 2023) - Pannus, Pieter; Depickère, Stéphanie; Kemlin, Delphine; Georges, Daphnée; Houben, Sarah; Olislagers, Véronique; Waegemans, Alexandra; De Craeye, Stéphane; Francotte, Antoine; Chaumont, Félicie; Van Oostveldt, Celien; Heyndrickx, Leo; et al.
Abstract: Background: Nursing home residents, a frail and old population group, respond poorly to primary mRNA COVID-19 vaccination. A third dose has been shown to boost protection against severe disease and death in this immunosenescent population, but limited data is available on the immune responses it induces. Methods: In this observational cohort study, peak humoral and cellular immune responses were compared 28 days after the second and third doses of the BNT162b2 mRNA COVID-19 vaccine in residents and staff members of two Belgian nursing homes. Only individuals without evidence of previous SARS-CoV-2 infection at third dose administration were included in the study. In addition, an extended cohort of residents and staff members was tested for immune responses to a third vaccine dose and was monitored for vaccine breakthrough infections in the following six months. The trial is registered on ClinicalTrials.gov (NCT04527614). Findings: All included residents (n = 85) and staff members (n = 88) were SARS-CoV-2 infection naïve at third dose administration. Historical blood samples from 28 days post second dose were available from 42 residents and 42 staff members. Magnitude and quality of humoral and cellular immune responses were strongly boosted in residents post third compared to post second dose. Increases were less pronounced in staff members than in residents. At 28 days post third dose, differences between residents and staff had become mostly insignificant. Humoral, but not cellular, responses induced by a third dose were predictive of subsequent incidence of vaccine breakthrough infection in the six months following vaccination. Interpretation: These data show that a third dose of mRNA COVID-19 vaccine largely closes the gap in humoral and cellular immune response observed after primary vaccination between NH residents and staff members but suggest that further boosting might be needed to achieve optimal protection against variants of concern in this vulnerable population group.